Image cytometric nuclear texture features in inoperable head and neck cancer - Strojan Fležar, Margareta (Radiology and oncology (Ljubljana), 2011)
Background. Image cytometry can measure numerous nuclear features which could be considered a surrogate end-point marker of molecular genetic changes in a nucleus. The aim of the study was to analyze image cytometric nuclear featuresin paired samples of primary tumor and neck metastasis in patients with inoperable carcinoma of the head and neck. Materials and methods. Image cytometric analysis of cell suspensions prepared from primary tumor tissue andfine needle aspiration biopsy cell samples of neck metastases from 21 patients treated with concomitant radiochemotherapy was performed. Nuclear features were correlated with clinical characteristics and response to therapy. Results. Manifestation of distant metastases and new primaries was associated (p<0.05) with several chromatin characteristics from primary tumor cells, whereas the origin of index cancer and disease response in the neck wasrelated to those in the cells from metastases. Many nuclear features of primary tumors and metastases correlated with the TNM stage. Conclusions. A specific pattern of correlation between well-established prognostic indicatorsand nuclear features of samples from primary tumors and those from neck metastases was observed. Image cytometric nuclear features represent a promising candidate marker for recognition of biologically different tumor subgroups.
Keywords: diagnostika; glava; neoplazme; prognoza; radiologija; rak (medicina); slikovna citometrija; vrat; Vrata